A focussed single-view hand-held echocardiography protocol for the detection of rheumatic heart disease. (11th September 2017) - Diamantino, Adriana; Beaton, Andrea; Aliku, Twalib; Oliveira, Kaciane; Oliveira, Cassio; Xavier, Luciana; Perlman, Lindsay; Okello, Emmy; Nascimento, Bruno; Ribeiro, Antonio R. P.; Nunes, Maria C. P.; Sable, Craig
Abstract: Background: Echocardiographic screening represents an opportunity for reduction in the global burden of rheumatic heart disease. A focussed single-view screening protocol could allow for the rapid training of healthcare providers and screening of patients. Objective: The aim of this study was to determine the sensitivity and specificity of a focussed single-view hand-held echocardiographic protocol for the diagnosis of rheumatic heart disease in children. Methods: A total of nine readers were divided into three reading groups; each interpreted 200 hand-held echocardiography studies retrospectively as screen-positive, if mitral regurgitation ⩾1.5 cm and/or any aortic insufficiency were observed, or screen-negative from a pooled study library. The performance of experts receiving focussed hand-held protocols, non-experts receiving focussed hand-held protocols, and experts receiving complete hand-held protocols were determined in comparison with consensus interpretations on fully functional echocardiography machines. Results: In all, 587 studies including 76 on definite rheumatic heart disease, 122 on borderline rheumatic heart disease, and 389 on normal cases were available for analysis. The focussed single-view protocol had a sensitivity of 81.1%, specificity of 75.5%, negative predictive value of 88.5%, and a positive predictive value of 63.2%; expert readers had higher specificity (86.1 versus 64.8%, p<0.01) but equal sensitivity. Sensitivity – experts, 96% and non-experts, 95% – and negative predictive value – experts, 99% and non-experts, 98% – were better for definite rheumatic heart disease. False-positive screening studies resulting from erroneous identification of mitral regurgitation and aortic insufficiency colour jets increased with shortened protocols and less experience (p<0.01). Conclusion: Our data support a focussed screening protocol limited to parasternal long-axis images. This holds promise in making echocardiographic screening more practical in regions where rheumatic heart disease remains endemic.